Kinetics and Thermodynamics of Cr3+ Adsorption on Modified Palm Thread - Lv, Wengang; He, Bing; Zhou, Yanbo; Qiu, Haibing; Lu, Jun (Asian Journal of Chemistry, 2013)
Adsorption of Cr3+ from aqueous was studied by using a novel adsorbent i.e. (NaOH-PT), palm thread (PT) modified with sodium hydroxide. The electron microscopy, infrared spectroscopy and X-ray diffraction were used to analyze the sorbents before and after modification. The effects of initial pH and contact time on the adsorption were examined. The results showed that the adsorption capacity reached the maximum at pH of 6.0 and the adsorption reached the equilibrium about 8 h. At different temperatures, the adsorption kinetics was better meet the Lagergren pseudo second kinetic model. And the whole adsorption process was controlled by liquid film diffusion and particle diffusion. The adsorption isotherms were better fitted Langmuir adsorption model. According to the calculations of thermodynamic equation, DG < 0, DH = 35.4584 kJ mol-1, DS = 139.9828 J mol-1, those indicated that the adsorption was spontaneous, endothermic, entropy increase and belonged to chemical adsorption.